Spectral upper bounds on the size of k-regular induced subgraphs - Cardoso, D.M.
Convex quadratic programming upper bounds on the size of k-regular induced subgraphs are analyzed and a necessary and sufficient condition for such upper bounds being tight is introduced. Based on this approach, new spectral upper bounds on the order of maximum size k-regular induced subgraphs are deduced. Related open problems and a few computational experiments are presented. © 2009 Elsevier B.V. All rights reserved.